2021
DOI: 10.1039/d0cy02306j
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the water oxidation catalytic activity of iridium complexes by functionalizing the Cp*-ancillary ligand: hints on the nature of the active species

Abstract: The catalytic activity toward NaIO4 driven water oxidation of a series of [RCp*IrCl(µ-Cl)]2 dimeric precursors, containing tetramethylcyclopentadienyl ligands with a variable R substituent (H, 1; Me, 2; Et, 3; nPr,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 84 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…Iridium(III) chloride hydrate (99.9%) was purchased from Strem, while organic reactants were purchased from Alfa Aesar, Apollo Sci., and TCI Europe, and were of the highest purity available. Compounds 1a [ 34 ] and 1b–e [ 14 ] were synthesized according to the respective literature procedures. Unless otherwise specified, operations were conducted in air.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iridium(III) chloride hydrate (99.9%) was purchased from Strem, while organic reactants were purchased from Alfa Aesar, Apollo Sci., and TCI Europe, and were of the highest purity available. Compounds 1a [ 34 ] and 1b–e [ 14 ] were synthesized according to the respective literature procedures. Unless otherwise specified, operations were conducted in air.…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, a comprehensive evaluation of the effects of the modification of the Cp* ring has not been fully addressed hitherto. A recent study by some of us outlined that replacement of one methyl with a range of substituents deeply influences the catalytic activity of the resulting iridium(III) tetramethylcyclopentadienyl complexes in water oxidation, through a balance of electronic and steric factors [ 14 ]. Here, we report the synthesis of a series of piano-stool 2-phenylpyridyl complexes containing a {η 5 -C 5 Me 4 R} ligand with variable R, and a study of their in vitro anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are necessary to establish if different classes of ancillary ligands behave similar to the pic systems studied here. Nevertheless, it is important to note that, combining the observations discussed in the present study with those reported in the aforementioned literature studies on Cp* degradation, 59,60,[62][63][64][65][66]71 some important hints on the structure of the active species emerge. Indeed, this should consist of a likely multimetallic species containing fragments deriving from Cp* oxidative transformations and no other ancillary ligands of the parental precatalysts.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…By carrying out multiple NaIO 4 injection experiments, it was possible to demonstrate that the intrinsic activity of the final active species depends on the nature of the R-group, providing strong supporting evidence for the persistence of some Cp' degradation products in the coordination sphere of the active Ir centers. 71 These interesting results prompted us to explore the fate of the additional, non-Cp* ligands in Ir-WOCs under catalytic conditions, which has been far less explored in the literature. To this aim, pyridine-carboxylate (pic) ligands were selected as the case study.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[6,9,10] There are a large number of homogeneous Ir precatalysts for catalytic water oxidation. Many leading efforts to study these molecular Ir catalysts have focused on the use of chemical oxidants (e.g., NaIO 4 and ceric ammonium nitrate), [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] with perhaps fewer studies on electrochemically driven water oxidation. [25][26][27][28][29] For example, Crabtree and coworkers identified the tris-aqua complex [Cp*Ir(H 2 O) 3 ] 2 (A) (Cp* ¼ pentamethylcyclopentadienyl) and the complex bearing the 2-(2-pyridyl)-2-propanolate ligand, B, as molecular water oxidation catalyst precursors at pH 7 and 1.7 V versus normal hydrogen electrode…”
Section: Introductionmentioning
confidence: 99%